2019
DOI: 10.1002/jcb.28727
|View full text |Cite
|
Sign up to set email alerts
|

Low‐intensity pulsed ultrasound promotes bone morphogenic protein 9‐induced osteogenesis and suppresses inhibitory effects of inflammatory cytokines on cellular responses via Rho‐associated kinase 1 in human periodontal ligament fibroblasts

Abstract: Periodontal ligament fibroblasts (PDLFs) have osteogenic capacity, producing bone matrix proteins. Application of bone morphogenic proteins (BMPs) to PDLFs is a promising approach for periodontal regeneration. However, in chronic bone metabolic disorders, such as periodontitis, proper control of accompanying inflammation is essential for optimizing the effects of BMPs on PDLFs. We have previously shown that low‐intensity pulsed ultrasound (LIPUS), a medical technology that induces mechanical stress using sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Low‐intensity pulsed ultrasound (LIPUS) is a non‐invasive ultrasound stimulus that could enhance fracture and non‐union bone healing 21 . It could enhance tissue repair and regeneration by inducing osteogenic differentiation of cells, producing more calcium deposits, and promoting the secretion of cytokines and ECM 22‐24 . Previous studies by our research group have demonstrated that LIPUS can attenuate lipopolysaccharide‐induced inflammation of PDLC 25 and improve its osteogenic differentiation, 26,27 which has great significance for regenerative treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Low‐intensity pulsed ultrasound (LIPUS) is a non‐invasive ultrasound stimulus that could enhance fracture and non‐union bone healing 21 . It could enhance tissue repair and regeneration by inducing osteogenic differentiation of cells, producing more calcium deposits, and promoting the secretion of cytokines and ECM 22‐24 . Previous studies by our research group have demonstrated that LIPUS can attenuate lipopolysaccharide‐induced inflammation of PDLC 25 and improve its osteogenic differentiation, 26,27 which has great significance for regenerative treatment of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…21 It could enhance tissue repair and regeneration by inducing osteogenic differentiation of cells, producing more calcium deposits, and promoting the secretion of cytokines and ECM. [22][23][24] Previous studies by our research group have demonstrated that LIPUS can attenuate lipopolysaccharide-induced inflammation of PDLC 25 and improve its osteogenic differentiation, 26,27 which has great significance for regenerative treatment of periodontitis. Since LIPUS affects the synthesis of ECM proteins in cells and bone tissue repair, we hypothesized that LIPUS can stimulate the formation of hPDLSC sheets (hPDLSCSs) and affect their osteogenic differentiation, further improving periodontal tissue regeneration.…”
mentioning
confidence: 99%
“…An acidic environment in the oral cavity could also lead to an increased chemical reactivity of the restorative materials; this could be caused by the uptake of acidic beverages or inflammatory reactions in the oral cavity (i.e., periodontitis) [ 12 , 13 ]. Several studies have shown that subjects with periodontitis have significantly higher salivary levels of cytokines, acidic substances, and reactive oxidative stress molecules [ 12 , 13 , 34 , 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…LIPUS treatment is an emerging physical therapy for the bone, nerve, and muscle disorders (15). Available studies have confirmed that it can suppress inflammation, promote osteogenesis and facilitate the ossification of hypertrophic chondrocytes (16,17). This study investigated and compared the effects of LICU and LIFU on the bone formation in rabbits.…”
Section: Discussionmentioning
confidence: 99%